Tathwir wasilat fidiu al-rasum al-mutaharika limawad al-istima' fi ta'lim al-lughah al-'arabiyah fi al-saff al-'ashir bil-madrasah al-'aliyah al-jihad Buanjin Luwu al-Shamaliyah - Alfiani Wahid; Kartini; Alfan Putra (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
This research aims to describe the development of an animated video tool for listening materials in teaching Arabic language in the tenth grade at Al-Jihad High School in Buanjin, and to describe the effectiveness of the animated video tool for listening materials in teaching Arabic language in the tenth grade at Al-Jihad High School in Buanjin. This research relies on the ADDIE model, which consists of (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. This research was conducted at Al-Jihad High School in Northern Buanjin by involving 9 respondents from August to September 2022 to determine the feasibility level of the learning tool. The results of this developmental research are: (1) Animated video products that contain educational materials and animations for students and teachers, attractive presentations, and training questions; (2) The feasibility level of the multimedia learning tool based on audiovisual Arabic language for tenth-grade students was rated by media experts with an overall average of 74% in the